Predominance of serum antibodies to synthetic peptide stemming from HPV 18 open reading frame E2 in cervical adenocarcinoma. Issue 6 (June 1992) - Lehtinen, M; Leminen, A; Paavonen, J; Lehtovirta, P; Hyöty, H; Vesterinen, E; Dillner, J
Abstract : AIMS: To determine if there are type specific differences in serum antibody responses to synthetic peptides derived from human papillomavirus (HPV) open reading frame (ORF) E2 in patients with cervical carcinoma. METHODS: Diagnostic phase sera from 88 age-matched women with cervical adenocarcinoma (AC), cervical squamous cell carcinoma (SC), ovarian cancer (OC) or no gynaecological malignancy were available. Serum IgG and IgA antibodies to synthetic peptides corresponding to a residue of HPV 6, 11, 16, and 18 ORF E2 18 amino acids long and a control peptide from mumps virus were determined by ELISA. RESULTS: Both IgA and IgG antibody positivity to the HPV 18 peptide were associated with increased risk (9.0-fold, confidence limits 1.5-199) for AC. IgA positivity to HPV 11, 16, and 18 peptides was associated with an increased risk for SC. However, the association of IgG antibodies to HPV 16 peptide with SC was not significant. IgA or IgG antibodies to HPV 6 or mumps virus peptides were not associated with increased risk for AC, SC, or OC. CONCLUSIONS: These results suggest a specific role for HPV 18 in AC. Differences in antibody responses to HPV peptide in AC and SC suggest immunopathogenetic differences between the two types of cervical carcinoma.